GAYA BAHASA PADA TEKS LIRIK LAGU RANDAI RANTAU KUANTAN - Herliya, Leni Kurnia; Rahman, Elmustian; Auzar, Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study discusses the style of language in the text song lyrics randai Overseas Kuantan.Tujuan this study is to describe the kinds of figure of speech or style of any language contained in the text song Randai Overseas Kuantan. The shape of this research is descriptive qualitative. The method is a qualitative descriptive analysis of words or phrases not in the form of figures and aims to describe the state of the object under study at the time the study was conducted. Sources of data in this study is the song randai Overseas Kuantan. Data collection techniques in the text song randai Overseas is a quote Kuantan or corpus consisting of sentences that contain phrases and language style. Stylistic use of language is typically to obtain the value of art works made. Style of language in general, there are four: (1) stylistic comparison (2) conflict style (3) style assertion (4) style satire. Based on these results we can conclude the text of the song lyrics randai Overseas Kuantan authors found that four types of language style. This is evident from the data obtained.Keyword: Style Language, Text randai lyrics Overseas Kuantan